Optimization of Using Moringa Oleifera Seed Powder as a Coagulant in the Treatment of Water Turbidity - Abbas, Saad Abdulamir (2001)
Moringa Oleifera has a great potential in water treatment. Several researchers have reported on its various uses as a coagulant. Moringa oleifera seed was found, able to achieve 83% turbidity removal. The active ingredient in Moringa oleifera seeds is a polypeptide, which acts as cationic polymer. The class of coagulants and flocculants known as polyelectrolytes (or polymers) is becoming more and more popular. A proper dosage of the right polyelectrolyte can improve finished water quality while significantly, reducing sludge volume and overall operating costs. Some studies have focused mainly on the efficiency of Moringa oleifera seed extract as a coagulant. Some other studies have focused on quality of water treated by coagulation using two forms of seed (shelled and unshelled) using the water extract with turbid water model as the water source. Other study investigates the effects of fully extracting oil from Moringa oleifera on its coagulation effectiveness using turbid water from surface water as the raw water source. There is a limitation in the primary coagulant characteristic of the protein, which exists in Moringa oleifera seed, as cationic polyelectrolytes when used to treat and remove water turbidity. This study investigate the optimum value of extracting oil from Moringa oleifera seed, and determine the effect of applying Moringa oleifera on treatment and removal of water turbidity. The seed of Moringa oleifera is processed by dehulling the coats and wings using Satake Rice Machine. Extraction of oil by hexane is carried out using cycles of extraction in Soxhlet apparatus. Several grads of oil extraction such as 20, 25 and 27% oil removal were applied to turbid water of different turbidity values as low, medium and high. The optimum value, which was observed at 25% oil removal, was applied to surface water samples of two river water namely, Batang Kali River and Selangor River. The results were significant for both model and surface water. In which, achievement up to 99% of turbidity removal was observed. The result of this study supports the new trend for cheap and more environmental friendly ways of water treatment This study exhibits a potential of using the Moringa oleifera as an alternative to conventional commercial coagulants.